Direct Detection of Mycobacterium bovis in Bovine Lymph Nodes by PCR - Cardoso, M. A.; Cardoso, R. F.; Hirata, R. D. C.; Hirata, M. H.; Leite, Clarice Queico Fujimura [UNESP]; Santos, A. C. B. [UNESP]; Siqueira, V. L. D.; Okano, W. [UNESP]; Rocha, N. S. [UNESP]; Lonardoni, M. V. C. (Wiley-Blackwell Publishing, Inc, 2009)
P>Thirty-five lymph node samples were taken from animals with macroscopic lesions consistent with Mycobacterium bovis infection. The animals were identified by postmortem examination in an abattoir in the northwestern region of state of Parana, Brazil. Twenty-two of the animals had previously been found to be tuberculin skin test positive. Tissue samples were decontaminated by Petroff's method and processed for acid-fast bacilli staining, culture in Stonebrink and Lowenstein-Jensen media and DNA extraction. Lymph node DNA samples were amplified by PCR in the absence and presence (inhibitor controls) of DNA extracted from M. bovis culture. Mycobacterium bovis was identified in 14 (42.4%) lymph node samples by both PCR and by culture. The frequency of PCR-positive results (54.5%) was similar to that of culture-positive results (51.5%, P > 0.05). The percentage of PCR-positive lymph nodes increased from 39.4% (13/33) to 54.5% (18/33) when samples that were initially PCR-negative were reanalysed using 2.5 mu l DNA (two samples) and 1 : 2 diluted DNA (three samples). PCR sensitivity was affected by inhibitors and by the amount of DNA in the clinical samples. Our results indicate that direct detection of M. bovis in lymph nodes by PCR may be a fast and useful tool for bovine tuberculosis epidemic management in the region.
Keywords: Mycobacterium bovis; lymph nodes; bovine tuberculosis; diagnosis; PCR; culture